2000
DOI: 10.1590/s0074-02762000000200006
|View full text |Cite
|
Sign up to set email alerts
|

Mepraia spinolai in the Southeastern Pacific Ocean Coast (Chile) - First insular record and feeding pattern on the Pan de Azúcar Island

Abstract: In a field collection performed at Pan de Azúcar Island in Northern Chile (Miles 1976, Schenone et al.1980, Schofield et al. 1982, Apt & Reyes 1986, Sagua 1988, Schenone & Rojas 1989, Lent et al. 1994.M. spinolai is the only specie of Triatominae with wing polymorphism. It is an aggressive insect which will feed on any host, even during daylight (Gajardo-Tobar 1953, Lent & Wygodzinsky 1979, Sagua 1983, Frías et al. 1987, Canals et al. 1998. It is almost entirely sylvatic, and only occasionally reported at home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Our study shows that both dispersal and vicariance hypotheses are not exclusive and have played major roles in the biogeographic origin of individuals of Mepraia in islands of northern Chile. Sagua et al [10] suggested that the occurrence of individuals of M. parapatrica in Pan de Azúcar Island could be explained through passive transport by marine birds. Mepraia species have opportunistic habits, being able to feed on birds both in the continent [40,41] and in the island [10].…”
Section: Biogeographic Origin Of Island Triatomines Of Northern Chilementioning
confidence: 99%
See 4 more Smart Citations
“…Our study shows that both dispersal and vicariance hypotheses are not exclusive and have played major roles in the biogeographic origin of individuals of Mepraia in islands of northern Chile. Sagua et al [10] suggested that the occurrence of individuals of M. parapatrica in Pan de Azúcar Island could be explained through passive transport by marine birds. Mepraia species have opportunistic habits, being able to feed on birds both in the continent [40,41] and in the island [10].…”
Section: Biogeographic Origin Of Island Triatomines Of Northern Chilementioning
confidence: 99%
“…Sagua et al [10] suggested that the occurrence of individuals of M. parapatrica in Pan de Azúcar Island could be explained through passive transport by marine birds. Mepraia species have opportunistic habits, being able to feed on birds both in the continent [40,41] and in the island [10]. Triatomines hidden in cracks may be attracted to birds and make their way between the feathers to feed; they may attach to the feathers and the stylet would pricks the skin.…”
Section: Biogeographic Origin Of Island Triatomines Of Northern Chilementioning
confidence: 99%
See 3 more Smart Citations